2014
DOI: 10.1016/j.schres.2013.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Preservation and compensation: The functional neuroanatomy of insight and working memory in schizophrenia

Abstract: BackgroundPoor insight in schizophrenia has been theorised to reflect a cognitive deficit that is secondary to brain abnormalities, localized in the brain regions that are implicated in higher order cognitive functions, including working memory (WM). This study investigated WM-related neural substrates of preserved and poor insight in schizophrenia.MethodForty stable schizophrenia outpatients, 20 with preserved and 20 with poor insight (usable data obtained from 18 preserved and 14 poor insight patients), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 39 publications
(48 reference statements)
1
24
0
Order By: Relevance
“…Similarly, bilateral cerebellum showed increased activity with load for both verbal and abstract stimuli, [43] and in participants with schizophrenia, Sapara demonstrated greater activation of bilateral cerebellum during a WM task, relative to healthy controls [57]. These data support the concept of a necessary compensatory activation in regions such as the There are some limitations to this study.…”
Section: Resultssupporting
confidence: 67%
“…Similarly, bilateral cerebellum showed increased activity with load for both verbal and abstract stimuli, [43] and in participants with schizophrenia, Sapara demonstrated greater activation of bilateral cerebellum during a WM task, relative to healthy controls [57]. These data support the concept of a necessary compensatory activation in regions such as the There are some limitations to this study.…”
Section: Resultssupporting
confidence: 67%
“…Compared to anterior cortical regions, much less is known about the involvement of posterior medial cortices due to the dearth of research into the contributions of these brain regions to various aspects of psychotic disorders[ 25 ]. In our recent study, we found further evidence of functional contributions from the precuneus, as well as the cerebellum, in supporting neural activities sub-serving the preservation of insight in schizophrenia patients[ 49 ].…”
Section: Discussionmentioning
confidence: 96%
“…Since then, several studies[ 26 , 30 , 31 , 47 ], including this one, have reported frontal neuroanatomical abnormalities in relation to impaired clinical insight in schizophrenia. Some functional imaging studies have further associated aberrant frontal functional MRI activity with impaired clinical insight during working memory[ 49 ], self-reflection[ 50 ], self-monitoring[ 51 ] and self-awareness tasks[ 52 ] in schizophrenia. In addition, earlier correlational VBM studies have also reported associations between smaller superior and middle temporal lobe grey matter volumes and impaired clinical insight[ 23 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of functional imaging studies, converging evidence has now linked poor insight to activity in central midline structures, including basal ganglia 104 , prefrontal cortex 103,104,[115][116][117] , cingulate cortex 103 , insula 117 , inferior parietal lobule 103 and the precuneus 116 . Functional resting state studies also suggest that insight may be related to the default mode network, particularly in the left hemisphere 102 .…”
Section: Abnormalities In Brain Function As a Root Of Poor Insightmentioning
confidence: 99%